Assessment of the Regional Government's Efficiency - Fedorova, Elena Anatolyevna; Chernikova, Lyudmila Ivanovna; Musienko, Svetlana Olegovna (Economy of Regions, 2019)
The article analyses domestic and foreign practice of assessing the regional government's efficiency. It also examines the legislative framework that regulates such assessment. Based on the analysis' results we propose measures to improve the regulatory framework. The research hypothesis is that the current methodology for assessing the regional government's efficiency cannot comprehensively reflect the real situation. Considering additional factors of social and innovative development, which mostly impact the gross domestic product as the main performance indicator of a region, will increase the effectiveness of the regional government. Using regression analysis, we determined, how much the indicators used for calculating the regional government's efficiency in accordance with the legislative framework, influence the gross regional product. We also analysed additional factors that significantly impact the gross regional product. In addition, we built a comprehensive model for assessing the regional government's efficiency based on the linear regression method. The research has shown that the current legislative framework does not include a complete list of factors that affect the regions development. Furthermore, the criteria for defining the most efficient regions (that receive additional grant support based on the assessment) do not allow implementing the stimulating function for these measures. The current procedure for grant support allocation to the most efficient regions leads to the increase of the regional development's differentiation. We provide a number of proposals for supplementing and improving the methodology for the regional government's efficiency, which are based on including additional factors that allow a comprehensive assessment of the regional management's efficiency. The study's results can be used for justifying the changes and amendments to the current legislative acts.